Risk management post financial crisis a period of monetary easing - Wagner, Niklas F., 1969-; Batten, Jonathan (Contemporary studies in economic and financial analysis ;, 2014)
Volume 96 of Contemporary studies in economic and financial analysis provides further insights to post-crisis developments in the global economic and financial environment. Risk management post financial crisis : a period of monetary easing includes papers from leading authors from central banks, world-renowned universities and international organisations. Topics and issues addressed by this volume include: an overview of advances in risk management in the post financial crisis environment, the impact that complexity present in financial returns now plays in measuring reporting and risk, the role that sentiment and herding plays in distorting prices in financial markets, the pro-cyclical impact of Basel III including effects on capital requirements and bank balance sheets, central bank monetary policies and bank liquidity in a world without quantitative easing, credit risk assessment and bank lending, and changes in the structure of international financial markets, including the rise and impact of financial markets in China and those financial products denominated in RMB.